Association between balance ability and cardiovascular disease onsets among middle-aged and older adults: an observational cohort study from the China Health and Retirement Longitudinal Study - Lin, Yinghe; Zhong, Shanshan; Sun, Zhihua (Frontiers in Public Health, 2025)
BackgroundPrevious studies showed the association between poor balance ability and a high risk of cardiovascular disease (CVD) mortality. However, there is little evidence regarding balance function and the onset of CVD. We aimed to examine the relationship between the balance ability and incident CVD risk.MethodsThis study retrospectively included participants (≥45 years) without CVD at baseline from the China Health and Retirement Longitudinal Study (CHARLS) in 2011 and those who were followed up in 2018. CHARLS used the semi-tandem stand test to assess balance ability. CVD was defined as the presence of physician-diagnosed heart disease and/or stroke. Cox proportional hazards models (considering competing risks) and stratification analysis were used to determine the association between balance ability and incident CVD risk.ResultsThe median age of the 10,154 participants was 57.0 (51.0, 64.0) years old, with 51.0% female. Compared to those with good balance ability, individuals with moderate balance ability had a higher risk of incident CVD [HR (95% CI): 1.15 (1.03–1.28)], and the risk was more pronounced in female (20.0%), rural residence (21.0%), never smoking (22.0%), never drinking (23.0%), hypertension (16.0%), without dyslipidemia (17.0%), and without kidney disease (13.0%) participants. After multiple imputations of metabolic biomarkers data, the results of sensitivity analyses were generally consistent.ConclusionLower balance ability was associated with an increased risk of incident CVD among middle-aged and older Chinese adults. The simple, economical, effective, and safe physical measurements of balance function deserve further investigation in public health.